Treatment adherence, persistence, and effectiveness of fixed dose combination versus free combination therapy of rosuvastatin–ezetimibe as a lipid-lowering therapy - Samnaliev, Mihail; Khan, Irfan; Potukuchi, Praveen; Lee, Kelly; Garon, Genevieve; Nicholls, Charlie (Frontiers in Cardiovascular Medicine, 2025)
BackgroundGuidelines for dyslipidemia management recommend adding ezetimibe for patients with dyslipidemia inadequately controlled with statin monotherapy. A fixed-dose combination (FDC) of statin and ezetimibe may improve persistence and adherence and hence reduce LDL-C further compared to free-combination treatment (FCT). The primary aim was to compare persistence/adherence with FDC versus FCT of rosuvastatin and ezetimibe (R/E); the secondary aim was to assess the impact of treatment adherence and persistence to LDL-C percentage reduction from baseline. An exploratory analysis assessed the impact of treatment adherence and persistence to incidence of major adverse cardiovascular events (MACEs). A subgroup analysis of patients on FDC of rosuvastatin 10 mg and ezetimibe 10 mg was also conducted.MethodsA retrospective analysis was performed using the THIN® database from Belgium and France in individuals (aged ≥18 years who received R/E as FDC or FCT between January 01, 2017, and November 30, 2022). Persistence (time from landmark date to discontinuation, with the latter defined as >45 days gap between prescription fills) and adherence (having a proportion of days covered ≥80%) were defined. Subsequent analyses adopted propensity score matching or weighting, followed by Cox and logistic regression models.ResultsA total of 15,643 treatment episodes (FDC: 11,300; FCT: 4,343) were selected. FDC R/E was associated with greater persistence (HR: 0.54, 95% CI: 0.51–0.58) and higher odds of adherence (OR: 3.00, 95% CI: 2.70–3.30) than FCT R/E. Based on the regression analysis results, patients who were persistent to treatment had a 10% higher reduction in LDL-C values from baseline than those non persistent. Similarly, patients who were adherent had 9.6% higher reduction in LDL-C levels from baseline than those not adherent. No significant difference was observed in association between persistence/adherence and MACEs. A consistent trend was also observed in the subgroup analysis.ConclusionsIn conclusion, FDC of R/E use was associated with higher treatment persistence and adherence than FCT of R/E. Patients persistent/adherent to treatment had greater LDL-C reductions than those who discontinued or did not follow treatment schedule. The limited number of MACEs suggests a cautious interpretation of exploratory MACE findings.